Weakened - Prashalini, Naidu (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Weak, Disgusted, Damaged, so damaged, so weak that moving or walking seems like a wearisome task The heart vaults a substantial amount of pain, It takes over your entire being, obstructs your senses, You stay sprawled out on the bed, hair tousled, those detached eyes staring straight at the carnelian painted ceiling,